Patient satisfaction, health care resource utilization, and acute headache medication use with galcanezumab: results from a 12-month open-label study in patients with migraine - Ford, Janet H (Patient Prefer Adherence, 2018)
BACKGROUND: Effects of galcanezumab, a monoclonal antibody against calcitonin gene-related peptide, on patient satisfaction, health care resource utilization (HCRU), and acute medication use were evaluated in a long-term, open-label study in patients with migraine. METHODS: Patients with episodic (78.9%) or chronic migraine (21.1%) were evaluated in the CGAJ study, an open-label study with 12-month treatment period. Galcanezumab 120 mg (with a loading dose of 240 mg) or 240 mg was administered subcutaneously once a month during treatment period. A self-rated scale, Patient Satisfaction with Medication Questionnaire–Modified (PSMQ-M), was used to measure satisfaction levels. Participants reported HCRU for the previous 6 months at baseline and that which occurred since the patient’s last study visit during treatment period. Acute headache medication use for migraine or headache for the past month was self-reported by participants at baseline and at each monthly visit during treatment period. RESULTS: At Months 1, 6, and 12, at least 69% of patients treated with galcanezumab responded positively for overall satisfaction, preference over prior treatments, and less impact from side effects. There were within-group reductions from baseline in migraine-specific HCRU (per 100 person-years) with galcanezumab for health care professional visits (173.4 to 59.6), emergency room visits (20.2 to 4.7), and hospital admissions (3.7 to 0.4) during treatment period. Statistically significant reductions in HCRU were observed for some events. There were significant within-group reductions from baseline in mean number of days/month with acute headache medication use for migraine or headache at each monthly visit during treatment period (overall change: −5.1 for galcanezumab 120 mg/240 mg; p<0.001). CONCLUSION: Results from this long-term, open-label study suggest that treatment with galcanezumab is likely to lead to high patient satisfaction with treatment as well as meaningful reductions in migraine-specific HCRU and acute headache medication use in people with migraine.